2021
DOI: 10.3389/fpls.2021.657300
|View full text |Cite
|
Sign up to set email alerts
|

Essential Roles of the Linker Sequence Between Tetratricopeptide Repeat Motifs of Ethylene Overproduction 1 in Ethylene Biosynthesis

Abstract: Ethylene Overproduction 1 (ETO1) is a negative regulator of ethylene biosynthesis. However, the regulation mechanism of ETO1 remains largely unclear. Here, a novel eto1 allele (eto1-16) was isolated with typical triple phenotypes due to an amino acid substitution of G480C in the uncharacterized linker sequence between the TPR1 and TPR2 motifs. Further genetic and biochemical experiments confirmed the eto1-16 mutation site. Sequence analysis revealed that G480 is conserved not only in two paralogs, EOL1 and EOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…This observation suggests functional redundancy among ACO genes in Arabidopsis , similar to what has been reported for the ACS gene family (Tsuchisaka et al ., 2009; Houben & Van De Poel, 2019). Previous studies have noted that the ethylene overproducing mutants eto1 and eto3 manifest phenotypic differences compared with WT exclusively in roots under light‐grown conditions (Rao et al ., 2002; Chen et al ., 2013; An & Gao, 2021). Correspondingly, our findings revealed that ACC accumulation in eto1 and eto3 as compared to WT was significant in roots, but not in shoots (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests functional redundancy among ACO genes in Arabidopsis , similar to what has been reported for the ACS gene family (Tsuchisaka et al ., 2009; Houben & Van De Poel, 2019). Previous studies have noted that the ethylene overproducing mutants eto1 and eto3 manifest phenotypic differences compared with WT exclusively in roots under light‐grown conditions (Rao et al ., 2002; Chen et al ., 2013; An & Gao, 2021). Correspondingly, our findings revealed that ACC accumulation in eto1 and eto3 as compared to WT was significant in roots, but not in shoots (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ethylene biosynthesis is repressed by ETHYLENE OVERPRODUCTION1 ( ETO1 ) (An & Gao, 2021). The study found that eto1 root hair was longer, while auxin‐resistant mutants ibr5 , tir1 , and axr1 inhibited the longer root hair phenotype compared with eto1 (Strader et al., 2010).…”
Section: Discussionmentioning
confidence: 99%